2002
DOI: 10.1159/000049409
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of the Puerperal Uterus: Correlation with Manual Examination

Abstract: Objectives: To document uterine involution after vaginal delivery and cesarean section by abdominal sonography and to compare the efficacy of manual examination and ultrasonography. Study Design: Postpartum manual and sonographic assessment of uterine involution was performed in 120 patients following vaginal and cesarean delivery with an attempt to build a database of changes in uterine dimensions. The patients’ reports on the intensity of uterine contractions and vaginal bleeding were compared to the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 4 publications
0
11
0
2
Order By: Relevance
“…There have been contradicting reports on the association between uterine size after cesarean deliveries in comparison to vaginal deliveries. In a study of 120 women, Shalev et al 13 found that the uterine length was significantly higher in women after cesarean deliveries compared to vaginal deliveries. They concluded that the uterine involution after vaginal delivery differs from that after cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…There have been contradicting reports on the association between uterine size after cesarean deliveries in comparison to vaginal deliveries. In a study of 120 women, Shalev et al 13 found that the uterine length was significantly higher in women after cesarean deliveries compared to vaginal deliveries. They concluded that the uterine involution after vaginal delivery differs from that after cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of blood, blood clots, necrotic decidua, membranes or gas can give various ultrasound images and a proper diagnosis is sometimes difficult. Nevertheless, the most common ultrasound finding associated with RPT is an echogenic mass 8,[34][35]55,[57][58][59][60][61][62][63][64][65][66][67][68] (Figs 9A to C, 10A and B, 11A and B, 12A, 13A to C and 14A). In contrast, Edwards et al 15 found in his study an echogenic mass on day 7 in 51% of normal cases, in 21% on day 14 and in 6% on day 21.…”
Section: Retained Placental Tissuementioning
confidence: 99%
“…Sa sensibilité est supérieure à l'examen clinique et à l'expression utérine. 16 Chez notre patiente, l'examen clinique ne démontrait pas de saignement. L'intérêt de l'échographie pelvienne est majeur en cas d'hémorragie survenant après une césarienne.…”
Section: Discussionunclassified
“…L'intérêt de l'échographie pelvienne est majeur en cas d'hémorragie survenant après une césarienne. 16 Les informations qu'elle apporte sont multiples. Dans une étude réalisée chez 125 patientes ayant une hémorragie de la délivrance, la présence d'une masse intra-utérine ou d'un épanchement intra-abdominal était associée à un mauvais pronostic.…”
Section: Discussionunclassified